Physical Activity Correlates in Middle School Adolescents: Perceived Benefits and Barriers and Their Determinants. (October 2019) - Roth, Sarah E.; Gill, Monique; Chan-Golston, Alec M.; Rice, Lindsay N.; Crespi, Catherine M.; Koniak-Griffin, Deborah; Cole, Brian L.; Upchurch, Dawn M.; Prelip, Michael L.
The purpose of this study was to examine the determinants of benefits and barriers and their relationship with physical activity (PA) among predominantly Latino middle school students. Data were collected in a cross-sectional survey of 4, 773 seventh-grade students recruited from a large, urban school district in Los Angeles. Hierarchical logistic regression models were used to assess determinants of benefits and barriers as well as their association with self-reported PA. Differences in benefits and barriers were observed by gender, ethnicity, and body size. Barriers were negatively correlated with all three PA outcomes while benefits were positively associated with exercising at least 60 min daily. A deeper understanding of benefits and barriers can facilitate the development of interventions and collaborative efforts among physical education teachers, school nurses, and administrators to implement comprehensive approaches that encourage students' participation in PA inside and outside of the classroom.